Features of the structure formation of secondary silicon carbide synthesized under conditions of the interaction of nano-sized nonstoichiometric silicon carbide with iron oxide - Tymoshenko, Yа.G.; Gadzyra, M.P.; Gnesin, G.G.; Galyamin, V.B. (Reports of the National Academy of Sciences of Ukraine, 2017)
The interaction between a nano-sized powder of a solid solution of carbon in silicon carbide and iron oxide at the high-temperature heating is studied. The phase composition and morphology of the powder product is analyzed. It is established that, in the process of interaction of a mixture of powders of the system (SiC-C) — Fe2O3 in vacuum, the synthesis of secondary SiC with a lattice parameter, which corresponds to the standard value of the cubic β-SiC, occurs. The same interaction in the flowing argon atmosphere is accompanied by the synthesis of secondary SiC with a decreased lattice parameter.